2022
DOI: 10.1039/d1ta08303a
|View full text |Cite
|
Sign up to set email alerts
|

Low full-cell voltage driven high-current-density selective paired formate electrosynthesis

Abstract: Anodic selective electro‐oxidation of methanol paring with cathodic carbon dioxide (CO2) reduction is regarded as a promising strategy to generate value added formate product. We firstly design a 3D‐assembled NiCo...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…The corresponding chronopotentiometry curves were shown in Figure S20. The comparison of total FEs and current densities between this study and other coupled electrolysis systems is shown in Figure d, demonstrating the obvious advantages of the paired electrolysis system developed in this work. …”
mentioning
confidence: 65%
“…The corresponding chronopotentiometry curves were shown in Figure S20. The comparison of total FEs and current densities between this study and other coupled electrolysis systems is shown in Figure d, demonstrating the obvious advantages of the paired electrolysis system developed in this work. …”
mentioning
confidence: 65%
“…Methanol oxidation reaction (MOR) to generate formate is the simplest and most reported alcohol oxidation reaction to couple with CO 2 RR. The recent developments are summarized in Table 1 [30,31,37,61–68] …”
Section: Co2rr Coupled With Value‐added Anodic Reactionsmentioning
confidence: 99%
“…As mentioned in the Introduction, if an electrocatalyst for selective CO 2 reduction to formate is used in the cathode, the concurrent production of formate can be realized (Figure 3a), eliminating the need for separate downstream purification of products from two sides [30,31,37,61–66] . For example, by using aligned InS nanorods and (oxy)hydroxide@np‐Ni 3 P as the cathode and anode catalysts, Zhang et al.…”
Section: Co2rr Coupled With Value‐added Anodic Reactionsmentioning
confidence: 99%
See 2 more Smart Citations